The phenomenon of aging in Algerian society - boualit, mouhamed (Journal of Social Sciences and Humanities, 2021)
Aged people represent a fundamental category in society, yet they are biologically vulnerable, and their particular vulnerability becomes even more serious whenever socio-economic, health and psychological aspects are taken into account. To preserve their social and psychological balance, after having played a leading role in society in the past, these people need to adapt to a set of conditions that are narrowly related to the previously mentioned aspects. However, their new status is governed by the law of human nature. Moreover, the ongoing change in society in general and in urban community in particular reshaped reality and gave it a completely new image as the ancient social systems along with the customs and traditions underwent a substantial change. Aged people were well-protected by those traditions, but today the situation is worsening more and more, especially in terms of social problems. Hence, all the institutions of society should give more importance to this category of people because they represent an integral part of the human community, and they should never be abandoned.